Faktor yang Mempengaruhi Kinerja Tenaga Kesehatan terhadap Pelayanan di Rumah Sakit Daerah Kalabahi Tahun 2023 - Makunimau, Sovie Iriani (MPI Press, 2023)
Background: The hospital is the main health facility for the community, so it is expected that the hospital has a good image (quality) in the eyes of its customers. This is largely determined by the quality of its human resources. Based on this educational background, SDMK is expected to be able to support quality hospital services. This is done to get health workers who are capable, skilled, qualified, and willing to achieve high work productivity and can deal with various problems and solve them intelligently, properly, and correctly. Based on the results of the interviews, it turned out that it was not by the desired expectations because of the declining health performance of workers so it had a direct impact on service. Objectives: The purpose of this study was to determine the motivational, leadership, and imbalance factors that affect the performance of health workers towards services at the Kalabahi Hospital in 2023. Method: The type of research used in this research is analytical quantitative research with a cross-sectional approach. The sample was obtained using total sampling obtained from the total population, namely all health workers working at the Kalabahi Regional Hospital in 2023 totaling 110 people. Data collection was carried out through face-to-face meetings with respondents by distributing questionnaires which were closed. In this analysis, the chi-square test was used to determine this effect using a significance level of 5% (0.05). Result: The results of the chi-square test research show that the motivation value (p=0.012), the appreciation value (p=0.024), and the leadership value (p=0.134). Conclusion: Motivational factors greatly influence the performance of health workers and also the majority of health workers whose performance is less good is greatly influenced by the reward factors they receive, thus influencing service performance. Meanwhile, leadership factors do not influence the performance of health workers at Kalabahi Hospital.